Identification of innate immune antiretroviral factors during in vivo and in vitro exposure to HIV-1 (2016)
Defensins, RNases and cytokines are present at mucosal barriers, main ports of HIV entry, and are potential mediators of the resistant phenotype exhibited by HIV-1-exposed seronegative individuals (HESN) during sexual exposure. We aimed to determine the role of soluble factors in natural resistance to HIV-1 infection. Vaginal/endocervical/oral mucosal samples were taken from 60 HESN, 60 seropositive (SP) and 61 healthy controls (HC). Human neutrophil peptide 1 (hNP-1), human beta defensin (hBD) 2 and 3, RNases, MIP-1ß and RANTES mRNA transcripts were quantified by qPCR and in vitro single-round, recombinant-based viral infectivity assay was used to evaluate the anti-HIV-1 activity of hBDs and RNases. HESN expressed significantly higher levels of hNP-1, hBDs mRNA in oral mucosa compared to HC (P < 0.05). In genital mucosa, significantly higher mRNA levels of MIP-1ß, RANTES and RNases were found in HESN compared to HC (P < 0.05). HBDs and RNases inhibit HIV-1 replication, particularly R5 at entry, reverse transcription and nuclear import of the viral life cycle. hNP-1, hBDs, MIP-1ß, RANTES and RNases, collectively could contribute to HIV-1 resistance during sexual exposure. Moreover, the inhibition of HIV-1 infection in vitro by hBDs and RNases suggests that they may be exploited as potential antiretrovirals. © 2015 Institut Pasteur.